Segregation analysis - Cannings, Chris; Teare, Dawn (Henry Stewart Talks, 2004)
Components of segregation analysis, Maximum likelihood models, Peeling and MCMC, Estimating the segregation proportion, Ascertainment/sampling bias, Ascertainment correction, Segregation analysis for quantitative traits, Polygenic models, Heritability, Components of variance, Genetic variance: additive and dominance, Epistatic variance, Analysis of covariance, Mixed models, Liability and threshold models, The hypergeometric polygenic model, Regressive models, Penetrance functions, Survival models, Computer packages
Archived at 2018/05/16